THE TETRODOTOXIN TOXICITY IN THE WHITE LEG SHRIMP LITOPENAEUS VANAMEI (BOONE, 1931) FEED BY TOXIC PUFFER IN REARING EXPERIMENT - Ha, Dao Viet; Ky, Pham Xuan; Anh, Nguyen Phuong (Vietnam Journal of Marine Science and Technology, 2014)
One-month old white leg shrimp Litopenaeus vanamei (Boone, 1931) was fed on the food pellet made from muscle and liver of the toxic puffer fish Torquigener gloerfelti for 4 months under rearing condition. The result of no difference of survive and growth rate between experimental and control one indicates that there was no negative effect from TTX contained food to the tested shrimp. There was a continuous increase in the toxicity of experimental L. vanamei during the rearing time (R2 = 0.97). After rearing for three months, TTX toxicity of L. vanamei reached the safety limit (10 MU/g), then 1.5 times higher in the end of experiment. On the other hand, after rearing for 4 months, 33.3 % individuals exhibited TTX toxicity higher than 10 MU/g, in which some of them showed very high toxicity (>100 MU/g). The results indicated that with a certain TTX amount from food supply, the product from cultured shrimp may cause poisoning to human. Therefore, using toxic puffer for feeding in aquaculture is not safety way.